2014
DOI: 10.1371/journal.pone.0104565
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 670 and 830 nm Red near Infrared Irradiation Therapy: A Comparative Study of Optic Nerve Injury, Retinal Degeneration, Traumatic Brain and Spinal Cord Injury

Abstract: Red/near-infrared irradiation therapy (R/NIR-IT) delivered by laser or light-emitting diode (LED) has improved functional outcomes in a range of CNS injuries. However, translation of R/NIR-IT to the clinic for treatment of neurotrauma has been hampered by lack of comparative information regarding the degree of penetration of the delivered irradiation to the injury site and the optimal treatment parameters for different CNS injuries. We compared the treatment efficacy of R/NIR-IT at 670 nm and 830 nm, provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 77 publications
2
41
1
1
Order By: Relevance
“…Nine percent excess penetration (i.e. 91 % absorption) from the surface of the skin (with hair intact) through all intervening tissue layers to the ventral surface of the spinal cord with a device delivering approximately 35 mW/cm 2 is consistent with a recent study that demonstrated an excess penetration of 6.6 % through the surface of the skin and the muscle overlying the spinal cord with a device producing approximately 16 mW/cm 2 in Fisher rat cadavers [9]. …”
Section: Discussionsupporting
confidence: 89%
“…Nine percent excess penetration (i.e. 91 % absorption) from the surface of the skin (with hair intact) through all intervening tissue layers to the ventral surface of the spinal cord with a device delivering approximately 35 mW/cm 2 is consistent with a recent study that demonstrated an excess penetration of 6.6 % through the surface of the skin and the muscle overlying the spinal cord with a device producing approximately 16 mW/cm 2 in Fisher rat cadavers [9]. …”
Section: Discussionsupporting
confidence: 89%
“…However, this technique was not useful in clinical settings because of its two critical drawbacks 1) it can not provide discrete information regarding the degree of penetration and 2) it lacks optimal treatment parameters for different CNS injury. Thus, further optimization in delivery devices, wavelength, intensity, and duration of R/NIR-IT is required to reconsider the laser therapy for different CNS injury types (Giacci et al, 2014). …”
Section: Axonal Injury Following Tbimentioning
confidence: 99%
“…Giacci et al. found that photobiomodulation was effective in two out of four in vivo rat models of CNS injury: partial optic nerve transection (effective), light‐induced retinal degeneration (effective), TBI (ineffective) and spinal cord injury (SCI, ineffective). They attributed these differences to lesser penetration of light in the case of TBI and SCI.…”
Section: Discussionmentioning
confidence: 99%